2018
DOI: 10.1177/2041669518780807
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Users’ Familiarity With the Objects Depicted in Icons on the Cognitive Performance of Icon Identification

Abstract: This study investigated the effects of users’ familiarity with the objects depicted in icons on the cognitive performance of icon identification. First, without knowing the specific semantic information of icons, 20 participants were required to search for target icons among visually similar distractors for 3-hour-long training sessions across 1 week, during which their familiarity with different icons was manipulated by differential exposure frequencies. Half of the icons were presented 10 times more often th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…We selected graphical symbols from computer and smart phone systems for reference, and then revised and created more than 300 icons for the following experiments. The method and instructions we used were similar to those adopted in previous studies (McDougall et al, 1999(McDougall et al, , 2000Shen et al, 2018). In this study, each icon was assigned a single Chinese word that five experts (experienced icon designers) agreed to be the best word label to represent the meaning of the icon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected graphical symbols from computer and smart phone systems for reference, and then revised and created more than 300 icons for the following experiments. The method and instructions we used were similar to those adopted in previous studies (McDougall et al, 1999(McDougall et al, , 2000Shen et al, 2018). In this study, each icon was assigned a single Chinese word that five experts (experienced icon designers) agreed to be the best word label to represent the meaning of the icon.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, to further explore this issue, we experimented with an icon visual search task across several days to simulate the effects of gaining increasing experience (Shen et al., 2018). After manipulating the participants’ level of familiarity with different icons, their ability to recall corresponding semantic information when cued with different icons was tested.…”
mentioning
confidence: 99%
“…A study by Shen [ 37 ] showed that people who are familiar with a restaurant, for example, could retrieve the situational information of the restaurant’s service from their memory, which directly affected their perception of the restaurant’s service. Another study by Shen [ 39 ] showed that a user’s familiarity with the objects depicted in a symbol affected their understanding of that symbol, suggesting that designers should use patterns and elements that are familiar to the users. Green [ 15 ] believed that it was difficult for individuals to draw symbols to represent unfamiliar situations during graphic generation.…”
Section: Related Researchmentioning
confidence: 99%
“…If a text label is included, it must be related to the functionality of the button, must be very descriptive to the driver, and must use vocabulary that is easily understood in the geographical context of use. Preferably, it should contain words that are universally understood [41][42][43][44][45][46][47].…”
Section: Solutionmentioning
confidence: 99%